Immigration and Labour: Australia and Canada Compared - Iacovetta, Franca; Quinlan, Michael; Radforth, Ian (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1996)
No persuasive account of labour in Australia and Canada can ignore the impact that immigration has wrought on the composition of the working class and preoccupations of workers, unions, and the varied political parties they have sponsored. Highlighting both similarities and differences between countries, the paper explores the paradoxical relationship that immigration has had with the labour movements of Australia and Canada. Although immigrants have been a critical source of union recruits, new ideas, and leaders (this being especially true for British skilled men), their presence was also long a source of concern, chauvinism, and division within predominantly white, Anglo-Celtic, and male-dominated union movements that adopted exclusionary policies, particularly regarding Asian and continental European workers. A more recent shift towards non-racist and inclusive policies unfortunately has not obliterated labour segmentation along racial and ethnic lines, especially job ghettos for immigrant women. Meanwhile, global restructuring and the loss of hard-earned union protections have increased immigrant workers' historic vulnerability. In explaining differences in the two countries — for example, Australia's greater 'success' at restricting non-white immigration before 1945 and Canada's earlier experience with a racially diverse work force — the paper cautions against easy generalizations, pointing instead to a series of historically contingent factors (such as 'accidents' of geography and differing political developments) that on some occasions led to rather different outcomes.